Extracellular vesicles of patients with acute-on-chronic liver failure induce mitochondrial dysfunction in T cells - Langer, Mona-May; Guckenbiehl, Sabrina; Bauschen, Alina; Stadler, Helena; Kaschani, Farnusch; Kaiser, Markus; Walkenfort, Bernd; Wedemeyer, Heiner; Lange, Christian M. (Frontiers in Immunology, 2025)
Background and AimsLiver cirrhosis and in particular acute-on-chronic liver failure (ACLF) are characterized by systemic inflammation and dysfunctional immune responses. Extracellular vesicles (EVs) are important mediators of cell stress and inflammation, but their role in ACLF is unclear.MethodsPhenotype and immune function of EVs of patients with compensated liver cirrhosis, acute decompensation, or ACLF were characterized regarding particle size, concentration, surface markers, and RNA cargo. In addition, functional analyses were performed to assess the impact of EVs on T cells.ResultsEVs of patients with liver cirrhosis showed lower expression of exosome-specific markers (e.g. CD9, CD63, CD81) than EVs of healthy individuals, carried a distinct cargo of proteins and small RNAs, and were in high frequency derived from liver cells based on their carriage of liver cell markers such as ASGPR1, CD248 or CD163. Of note, in ACLF the concentration of EVs decreased, and EVs in ACLF lost partially their differentiation and surface markers but were enriched in lncRNAs. In functional assays, EVs of patients with cirrhosis and ACLF induced changes in the composition of T cell populations like a loss of naïve and central memory T cells and an increase in effector memory T cells. Mechanistically, EVs decreased the viability of CD3+ T cells, which could be explained by an induction of mitochondrial dysfunction.ConclusionLiver cirrhosis is associated with distinct changes in circulating EVs. In ACLF, EVs are less differentiated and induce mitochondrial dysfunction, decreased T cell viability and changes in the composition of T cell populations.